RELATIONSHIP OF TUNA NETWORK BEHAVIOR WITH DENTAL AND MOUTH CLEANING STATUS IN COMMUNITIES PERTUNI IN BANDA ACEH CITY - Elfi Zahara; Andriani Andriani (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2019)
People with visual impairments usually show a higher index of debris, calculus and oral hygiene compared to normal people, this is because they have difficulty maintaining their dental and oral health, reaching access to dental care and also having difficulty receiving dental care. The purpose of this study was to determine the relationship of blind behavior to dental and oral hygiene status in the Pertuni Community in Banda Aceh City in 2018. With a total population of 42 respondents. This research is analytical and based on the results of statistical tests that there is no relationship of knowledge (p = 0.06), there is a relationship of attitude (p = 0.02) and there is a relationship of action (p = 0.01) with dental and oral hygiene status. It can be concluded that there is no relationship between knowledge with dental and oral hygiene status, and there is a relationship between attitudes and actions with dental and oral hygiene status. A good attitude is recommended to blind people to be able to change or improve behavior that is realized through a good action too.